MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN MELALUI PERMAINAN PUZZLE ANGKA PADA ANAK USIA 5-6 TAHUN DI TK PEMBINA NEGERI 1 BANGKO KABUPATEN ROKAN HILIR - Yusni Herlin; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Learning activities carried out in kindergarten Pembina State 1 Bangko only activities that cause children to experience difficulty in recognizing the concept of numbers, the children were able to mention the order number but were unable to recognize the concept of numbers. After making observations of research aims to determine through numbers puzzle game can see the children's ability to recognize the concept of numbers, to improve children's ability to recognize the concept of numbers, to measure how high the increase in numbers of children in a familiar concept, and to find creative ways to make learning a fun puzzle game in particular through the numbers. The method used is classroom action research, the number of children in this study were 17 people consisting of 8 boys and 9 girls. Based on the data of the percentage increase in the first cycle is 29.00% and the increase in cycle II reached 44.20% of all the data it can be concluded that the numbers through a puzzle game can improve the ability to know the concept of numbers in children aged 5-6 years in kindergarten Pembina State 1 Bangko Rokan Hilir.Keyword : Know ability Concepts Coat Numbers , Puzzle Figures